THE EFFECT OF ENTRY SELECTION PATH AND FAMILY ENVIRONMENT ON ACCOUNTING STUDENTS’ LEARNING ACHIEVEMENT WITH LEARNING MOTIVATION AS INTERVENING VARIABLE - Fransisca Dyah Anggraini (Erudio Journal of Educational Innovation, 2019)
This study discusses the Effects of Entrance Selection and Family Pathways on Accounting Learning Achievements with Learning Motivation as Intervening Variables in Student Musi Charistas Unika Palembang. The purpose of this study was to obtain empirical data on the influence of entrance selection, family environment and learning motivation as an intervening variable in students of the Accounting Study Program at UNIKA Musi Charitas Palembang. The sample used in this study was 140 students of the Accounting Study Program at UNIKA Musi Charitas Palembang.Technique sample collection in this research uses the method purposive sampling. The method of data analysis in this study uses path analysis (path analysis / AMOS). The test results show that, Entrance Selection Path (JSM) and Family Environment (LK) has a direct and significant effect on Learning Motivation (MB), Entrance Selection Path (JSM), Family Environment (LK), and Learning Motivation (MB) has a direct and significant effect on Learning Achievement (PB), Entrance Selection Path (JSM) and Family Environment (LK) has a positive and significant direct effect on Learning Achievement (PB) through Learning Motivation (MB) as an intervening variable. The advice for Higher Education should be to increase the quota for students accepted through the achievement path. Whereas for students with test paths it is recommended to increase their learning motivation so that the learning achievements obtained are not inferior to students from the scholarship track